The Mediating Role of Organizational Behavior in The Relationship Between Transformational Leadership, Managerial Competence of School Principal, and the Quality of Education: Evidence from Indonesian Public Elementary Schools - Dahlia, Ida; Sudadio, Sudadio; Rusdiyani, Isti (PPSDP International Journal of Education, 2025)
This study aims to analyze the direct and indirect effects of organizational culture, transformational leadership, and managerial competence on educational quality through organizational behavior in public elementary schools in Serang City, Indonesia. A quantitative study employing an ex-post facto survey design was conducted with a sample of 291 public elementary school teachers selected using proportionate stratified random sampling. Data were collected through validated Likert-scale questionnaires and analyzed using path analysis to examine direct and mediating relationships among variables. The results indicate that organizational culture (β = 0.033, p < 0.001), transformational leadership (β = 0.095, p < 0.001), and managerial competence (β = 0.469, p < 0.001) significantly influence organizational behavior, which fully mediates their effects on educational quality (R² = 0.976). Among the predictors, transformational leadership demonstrates the strongest total effect on educational quality. The findings suggest that improving educational quality requires integrated leadership development, enhancement of managerial competence, and strengthening organizational culture through interventions that foster positive organizational behavior in schools. This study introduces organizational behavior as a critical mediating variable that explains how leadership, culture, and managerial competence collectively translate into educational quality improvement in public elementary school settings. The study contributes to educational management literature by providing empirical evidence of a comprehensive mediation model and offering practical insights for policymakers and school leaders in designing evidence-based strategies for sustainable school quality improvement.